Graphene oxide-enhanced cytoskeleton imaging and mitosis tracking. Issue 23 (7th March 2017) - Li, Qian-Ru; Jiao, Jin-Biao; Li, Li-Li; He, Xiao-Peng; Zang, Yi; James, Tony D.; Chen, Guo-Rong; Guo, Lin; Li, Jia
Abstract : Graphene oxide enhances the imaging ability of a cell-impermeable peptide probe that targets microtubules, enabling the dynamic tracking of mitosis in live cells. Abstract : Here we show that graphene oxide greatly enhances the imaging ability of a peptide probe that selectively targets microtubules of the cytoskeleton, thus enabling the dynamic tracking of mitosis in live cells.